Blockchain-based relayer services: batching and submitting multiple energy transactions in a meta-transaction - Ma, Siteng (Nanyang Technological University, 2023)
Peer-to-peer energy trading has seen an increase of popularity with the adoption of smart grid and distributed energy resources in current days. Blockchain, a distributed ledger governed by consensus protocol, is deemed as a solid foundation to build the Peer-to-peer energy trading network on top of it where traceable and verifiable transaction logs become feasible.